2019
DOI: 10.1103/physreva.100.012126
|View full text |Cite
|
Sign up to set email alerts
|

Swift heat transfer by fast-forward driving in open quantum systems

Abstract: Typically, time-dependent thermodynamic protocols need to run asymptotically slowly in order to avoid dissipative losses. By adapting ideas from counter-diabatic driving and Floquet engineering to open systems, we develop fast-forward protocols for swiftly thermalizing a system oscillator locally coupled to an optical phonon bath. These protocols control the system frequency and the systembath coupling to induce a resonant state exchange between the system and the bath. We apply the fast-forward protocols to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 69 publications
0
44
0
Order By: Relevance
“…Introduction. With the advent of new quantum technologies, there is increasing interest in using small quantum systems to control and coherently manipulate mesoscopic environments [1][2][3][4][5][6]. In the simplest setting, a single spin- 1 2 qubit controls a surrounding bath of spins, extending the available degrees of freedom and turning the detrimental effects of the bath into a useful resource.…”
mentioning
confidence: 99%
“…Introduction. With the advent of new quantum technologies, there is increasing interest in using small quantum systems to control and coherently manipulate mesoscopic environments [1][2][3][4][5][6]. In the simplest setting, a single spin- 1 2 qubit controls a surrounding bath of spins, extending the available degrees of freedom and turning the detrimental effects of the bath into a useful resource.…”
mentioning
confidence: 99%
“…From a practical point of view, this setup is relevant for realistic experiments where the system undergoes a continuous periodic cycle with some external drives under the influence of environments. From a fundamental point of view, this setup allows one to better understand how CD could be effective in open system dynamics, which has not been explored intensively [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the fast thermalization of a harmonic oscillator has been proposed via the reverse engineering of a non-adiabatic Markovian master equation [43] and engineered dephasing [44]. A related study has shown the possibility of speeding up the thermalization of a system oscillator locally coupled to a harmonic bath [45]. Engineering of the system-bath coupling has also been proposed to speed-up isothermal processes [46].…”
mentioning
confidence: 99%